Food waste diversion for enhanced methane gas production at the Drake Water Reclamation Facility - Robbins, Cristian Arthur, author; Sharvelle, Sybil, advisor; Carlson, Kenneth, committee member; Keske, Catherine, committee member (Colorado State University. Libraries, 2012)
Food waste diversion to enhance methane gas production in municipal wastewater treatment plants is an emerging trend in the United States. The methane gas produced in anaerobic digesters of a municipal wastewater treatment plant can be used to produce renewable energy to meet electric and heating needs of the plant. The Drake Water Reclamation Facility in Fort Collins, Colorado is very interested in implementing energy generation from anaerobic digester biogas and a food waste diversion program. The objective of this study is to determine the efficacy and viability of implementing a food waste diversion program coupled with energy generation technology to provide electricity and heating generation to meet the plant's needs. A food waste characterization study of the Colorado State University's Ram's Horn Dining Facility processed food waste was conducted to determine important characteristics of a readily available food waste. An analysis of the operating capacity of the Drake Wastewater Reclamation Facility anaerobic digesters was conducted to determine the maximum amount of food waste that could be added on a daily basis. The maximum amount of food waste that could be added to the Drake Water Reclamation Facility anaerobic digesters is 37.5 tons per day. 2010 data for the Drake anaerobic digesters was analyzed and used as a baseline for analysis of the addition of various amounts of food waste ranging from 800 pounds of food waste per day to the maximum amount of 37.5 tons per day. The effects of the food waste on anaerobic digester biogas production and solids reduction in the digester were reported. Various technologies for generating energy from biogas were evaluated using reported cost data and characteristics. An economic analysis utilizing flared methane gas as fuel for the various technologies was completed which showed that microturbine and reciprocating engine technologies are economically viable options for the Drake Water Reclamation Facility to use for both electricity and heating generation. A triple bottom line analysis, with a rigorous economic analysis, of implementing a food waste diversion program at the Drake Water Reclamation Facility was conducted. Costs associated with a food waste processing facility and associated equipment was outlined and evaluated against the energy savings that enhanced methane gas production from various amounts of food waste addition provided. It was determined that it is not economically viable for the Drake Water Reclamation Facility to implement a food waste diversion program at this time. If energy prices rise and cost of equipment for a food waste diversion program decrease in the future, then the economics of this project may improve making it more viable.
Keywords: energy generation; wastewater treatment plant; food waste diversion; enhanced methane gas production; anaerobic digestion; biogas